2019
DOI: 10.3847/2041-8213/ab289d
|View full text |Cite
|
Sign up to set email alerts
|

Gas Accretion within the Dust Cavity in AB Aur*

Abstract: AB Aur is a Herbig Ae star hosting a well-known transitional disk. Because of its proximity and low inclination angle, it is an excellent object to study planet formation. Our goal is to investigate the chemistry and dynamics of the molecular gas component in the AB Aur disk, and its relation with the prominent horseshoe shape observed in continuum mm emission. We used the NOEMA interferometer to map with high angular resolution the J = 3-2 lines of HCO+ and HCN. By combining both, we can gain insight into the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 37 publications
(63 reference statements)
3
26
0
Order By: Relevance
“…Most species depicted ring-like emission co-spatial with the dust ring with a minimum towards the central dust gap, except 12 CO and HCO + . The higher angular resolution image of the HCO + 3→2 line reported by Rivière-Marichalar et al (2019) shows that within the dust cavity the HCO + emission is formed by a compact source towards the stellar position and at least one filament connecting the compact source with the outer ring. We concluded that the filamentary structure could be tracing an accretion flow from the outer ring into the inner disk.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…Most species depicted ring-like emission co-spatial with the dust ring with a minimum towards the central dust gap, except 12 CO and HCO + . The higher angular resolution image of the HCO + 3→2 line reported by Rivière-Marichalar et al (2019) shows that within the dust cavity the HCO + emission is formed by a compact source towards the stellar position and at least one filament connecting the compact source with the outer ring. We concluded that the filamentary structure could be tracing an accretion flow from the outer ring into the inner disk.…”
Section: Introductionmentioning
confidence: 89%
“…3.1). In addition to the data presented, we have included the profiles of the HCO + 3→2 and HCN 3→2 maps reported by Rivière-Marichalar et al (2019).…”
Section: Chemical Segregationmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 9 shows a comparison between the observed dust continuum emission at 1.3 mm (Tang et al 2012) and the dust distribution in e50-i60, where the dust over-density is seen as a large clump due to beaming effects. In addition, Rivière-Marichalar et al (2019) very recently reported the observation of clumps in HCN -a good tracer of cold and dense gas -around the inner edge of the disc. This supports the idea that the dusty clumps might be real.…”
Section: The Ab Aurigae Systemmentioning
confidence: 99%